Anthropometric Factors and Physical Condition Dominant Determinants Batting Skills in Softball - Saraya, Arif Eka (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2018)
Batting skills in softball requires several anthropometric factors and physical condition to play to improve skills. Anthropometric factors and physical condition, among others, height, arm length, arm muscle strength, hand-eye coordination, balance, and reaction time. This study aims to determine the anthropometric factors and the physical condition of the dominant determinant of batting skills in softball. This research approach uses a quantitative to design of confirmatory factor analysis. This study population is training student achievement softball in sports education university of riau. A sample of 100 people was obtained through a simple random sampling technique. The data used are taken through a series of tests of the independent and dependent variables. This research method through testing confirmatory factor KMO and Bartlett’s Test analysis using SPSS. Results from this research is: factor of anthropometri dominant physical condition and determinants batting skill in game of softball is arm length with value 0,788, arm muscle power with value 0,851 and time reaction of with value 0,737. The conclusion of this research is: factor of anthropometri dominant physical condition and determinants batting skill in game of softball is arm length, arm muscle power and time reaction ABSTRAKKeterampilan memukul dalam softball memerlukan beberapa faktor antropometrik dan kondisi fisik untuk bermain untuk meningkatkan keterampilan. Faktor antropometri dan kondisi fisik antara lain tinggi badan, panjang lengan, kekuatan otot lengan, koordinasi tangan-mata, keseimbangan, dan waktu reaksi. Penelitian ini bertujuan untuk mengetahui faktor antropometri dan kondisi fisik  yang dominan pada keterampilan memukul dalam softball. Pendekatan penelitian ini menggunakan kuantitatif dengan rancangan analisis faktor konfirmatori. Populasi penelitian ini adalah  mahasiswa yang mengikuti pelatihan softbal di pendidikan olahraga Universitas Riau. Sampel teriri dari 100 orang diperoleh melalui teknik simple random sampling. Data yang digunakan diambil melalui serangkaian tes variabel independen dan dependen. Metode penelitian ini melalui pengujian confirmatory factor KMO dan analisis Uji Bartlett menggunakan SPSS. Hasil dari penelitian ini adalah: faktor anthropometri dominan kondisi fisik dan determinan keterampilan memukul dalam permainan softball adalah panjang lengan dengan nilai 0,788, kekuatan otot lengan dengan nilai 0,851 dan waktu reaksi dengan nilai 0,737. Kesimpulan dari penelitian ini adalah faktor kondisi fisik dominan anthropometri dan determinan batting skill dalam permainan softball adalah panjang lengan, kekuatan otot lengan dan waktu reaksi.